Fruit dragée formulated with reused solution from pineapple osmotic dehydration - Sílvia Pimentel Marconi Germer; Gisele Marcondes Luz; Lidiane Bataglia da Silva; Marta Gomes da Silva; Marcelo Antonio Morgano; Neliane Ferraz de Arruda Silveira (Pesquisa Agropecuária Brasileira, 2017)
Abstract: The objective of this work was to evaluate the reuse of sucrose syrup in pineapple (Ananas comosus) osmotic dehydration and the application of the spent solution in fruit dragée formulation. Osmotic dehydration trials were performed in five cycles (65° Brix/45°C/3 hours), directly reusing the osmotic solution, with only one intermediate reconditioning step. Variations in osmotic solution properties and in dehydration parameters were observed, as well as a low microbial load in the system. The spent solution was rich in vitamin C (30 mg 100 g-1). Pineapple dragée covered with red fruits and acai powders were obtained with the reconditioned spent solution used as an adhesion solution. The dragée presented high levels of vitamin C (176 mg 100 g-1), polyphenols (154 mg GAE 100-1 g), carotenoids (220 μg 100 g-1), and potassium (330 mg 100 g-1). The product showed good sensory acceptance and purchase intention. Reusing sucrose syrup is technically feasible during pineapple osmotic dehydration, as is the application of the spent solution as an ingredient in fruit dragée production.